2023
DOI: 10.1101/2023.08.31.553629
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Matter Microstructural Plasticity Associated with Educational Intervention in Reading Disability

Steven L. Meisler,
John D. E. Gabrieli,
Joanna A. Christodoulou

Abstract: Children’s reading progress typically slows during extended breaks in formal education, such as summer vacations. This stagnation can be especially concerning for children with learning disabilities, such as dyslexia, because of the potential to exacerbate the skills gap between them and their peers. Reading interventions can prevent skill loss and even lead to appreciable gains in reading ability during the summer. White matter connections enable communication among the brain regions required for proficient r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 143 publications
0
5
0
Order By: Relevance
“…Furthermore, the accumulated evidence that the "reading brain" is plastic, and changes in ways specific to the reading programs used (Eden et al, 2004;Yoncheva, Wise, & McCandliss, 2015), has redoubled the importance of providing evidence-based reading instruction to developing readers. MBE research has also converged with theories of learning (e.g., dynamic skills theory; Fischer & Bidell, 2006) to reveal that skill acquisition is dynamic, with the impact of reading instruction differing by student and environmental characteristics, as well as by academic calendar phases (i.e., during summer vacation; Romeo et al, 2018;Meisler et al, 2023). Insights from studies on reading abilities among individuals with distinct neural architecture (e.g., relying on a single hemisphere as a consequence of epilepsy-related surgery) have likewise emphasized the resilience of students and the multiple pathways to reading progress (Christodoulou et al, 2021;Katzir, Christodoulou, & DeBode, 2017).…”
Section: Joanna a Christodouloumentioning
confidence: 99%
“…Furthermore, the accumulated evidence that the "reading brain" is plastic, and changes in ways specific to the reading programs used (Eden et al, 2004;Yoncheva, Wise, & McCandliss, 2015), has redoubled the importance of providing evidence-based reading instruction to developing readers. MBE research has also converged with theories of learning (e.g., dynamic skills theory; Fischer & Bidell, 2006) to reveal that skill acquisition is dynamic, with the impact of reading instruction differing by student and environmental characteristics, as well as by academic calendar phases (i.e., during summer vacation; Romeo et al, 2018;Meisler et al, 2023). Insights from studies on reading abilities among individuals with distinct neural architecture (e.g., relying on a single hemisphere as a consequence of epilepsy-related surgery) have likewise emphasized the resilience of students and the multiple pathways to reading progress (Christodoulou et al, 2021;Katzir, Christodoulou, & DeBode, 2017).…”
Section: Joanna a Christodouloumentioning
confidence: 99%
“…Reading interventions enhance brain activation of the typical reading network while engaging other cognitive systems to support reading (Perdue et al, 2022). Neuroplasticity is experience-dependent , in that high-quality reading experiences are necessary to strengthen core reading networks, without which brain infrastructure required for literacy may not develop efficiently (Luk & Christodoulou, 2023; Meisler et al, 2023). Notably, the majority of neuroplasticity research focuses on skill advancement (Perdue et al, 2022), though skill regression (Meisler et al, 2023) is possible.…”
Section: Summer Opportunity Through Brain Plasticitymentioning
confidence: 99%
“…Among intervention participants, students showed greater reading improvement and associated structural neuroplasticity if they started the program with more severe reading difficulties, and also if they came from lower SES backgrounds (Romeo et al, 2018). Across RD participants who did and did not receive reading intervention, decreases in reading scores over the summer were related to changes in the brain's white matter in key regions supporting language (left arcuate fasciculus and inferior longitudinal fasciculus), reflecting a potential neurocognitive signature of skill regression (Meisler et al, 2023).…”
Section: Summer Opportunity Through Brain Plasticitymentioning
confidence: 99%
“…Intervention studies have shown that an individual's academic environment can drive measurable changes in brain structure and function 28,29,31 . However, it remains unclear the extent to which educational opportunities uniquely influence brain development above and beyond other socioeconomic factors 12,16,19 .…”
Section: Exploring the Relationship Between Educational Opportunity A...mentioning
confidence: 99%
“…It bears mentioning that educational intervention studies have demonstrated that educational experiences can drive changes in brain structure and function over remarkably short timescales. These studies have shown that a short-term, intensive reading intervention led to changes across a range of white ma er tracts, including left arcuate and left ILF, and that these changes correspond to changes in reading skill [28][29][30] . In the domain of mathematics, intensive learning experiences have been shown to "normalize'' functional activity in students with mathematical learning difficulties 31 and participation in specific math curricula drives changes in neurotransmi er concentration in the middle frontal gyrus and predicts longitudinal changes in mathematical reasoning 32 .…”
Section: Introductionmentioning
confidence: 98%